Association and Occurrence of Bifidobacterial Phylotypes Between Breast Milk and Fecal Microbiomes in Mother–Infant Dyads During the First 2 Years of Life - Yan, Wenli; Luo, Baolong; Zhang, Xuyao; Ni, Yongqing; Tian, Fengwei (Frontiers in Microbiology, 2021)
Breast milk acts as an intermediary for the transfer of functionally important commensal bacteria from mother to infant, especially for Bifidobacterium that can colonize the infant gut. However, the vast majority of rRNA amplicon-based studies reported the conspicuous intercohort and interindividual variation for the prevalence of Bifidobacterium in breast milk. In order to elucidate whether Bifidobacterium phylotypes persistently co-occured at the species or strain level in mother–breast milk–infant triads, we analyzed collectively the next-generation sequencing (NGS) datasets of bacterial 16S rRNA gene and the Bifidobacterium-specific groEL gene from maternal feces, breast milk, and infant feces in a small yet very homogeneous cohort of 25 healthy Uyghur mother–infant pairs (lactation for 7–720 days) in Kashgar, Xinjiang, China. Overall, 16S rRNA gene analysis showed that microbiome in the newborn gut was closer to that of breast milk in the first 4 months of lactation, and subsequently showed an obvious trend of adulthood at 6–12 months. Based on the BLAST accurate taxonomic result of the representative sequences of all ASVs (amplicon sequencing variants), only three sets of ASVs could be clearly assigned into Bifidobacterium species, whereas the remaining eight sets of ASVs corresponded to four indefinite Bifidobacterium species group. By contrast, the groEL gene dataset was partitioned into 376 ASVs, at least belonging to 13 well-known Bifidobacterium species or subspecies, of which 15 ASVs, annotated to seven well-known Bifidobacterium species or subspecies, showed triadic synchronism in most 23 mother–infant pairs tested. However, several other rare bifidobacterial phylotypes, which were frequently encountered in animals, were found to display no correspondence of the presence between the three ecosystems of mother–infant pairs. Our test results were obviously to support the hypothesis that breast milk acts as an intermediary for the transfer of probiotic commensal bacteria from mother to infant, especially for endosymbiotic Bifidobacterium that can colonize the infant gut. Some oxygen-insensitive exogenous Bifidobacterium phylotypes with a cosmopolitan lifestyle may be indirectly transferred to breast milk and the infant’s intestinal tract through environmental contamination. Thus, the groEL gene proved to be a very effective target for the depth resolution of Bifidobacterium community by high-throughput sequencing technologies.